Heaviness, intensity, and intimacy: Dutch elder care in the context of retrenchment of the welfare state (Medicine Anthropology Theory, 2014)
In the Netherlands the recent shift to a ‘participation society’ has led to a reconfiguration of health care arrangements for long-term care. The new long-term care act, scheduled to commence January 2015, forms the political realization of the participation society: people are expected to decrease their dependency on state provisions and instead become self-sufficient or dependent on family and community solidarity. In this Think Piece we argue that the implicit references of policy makers to pre-welfare state community solidarity and self-sufficiency do not adequately consider the historical and social embeddedness of care. Referring to Rose’s concept of ‘politics of conduct’ we argue that in framing care as a moral obligation, the current politics of conduct may obscure the physical and psychological heaviness of intimate care between family members, the diversity of care relations, and their sociohistorical embeddedness.